Investigations on the Effect of Manganese Ions on the Structural and Optical Properties of ZnS Nanoparticles Synthesized by Solvo-thermal Route - John Kennady Vethanathan3, T.H. Freeda4, S. Meenakshi Sundar5, M. Brightson1, P. Selvarajan2* (Recent Research in Science and Technology, 2010)
Nanoparticles of Zinc Sulfide (ZnS) doped with manganese ions (Mn2+) with different ratios were synthesized by solvothermal route using a microwave oven. The X-ray diffraction patterns showed the typical interplanar spacings corresponding to the cubic phase. UV-visible optical spectroscopy study was carried out to determine the band gap energy of the nanocrystalline ZnS and ZnS:Mn particles. Variation of band gap energy with different ratios of Mn2+ was studied. ESR studies were carried out for the synthesized nanoparticles of this work and ‘g’ factor was determined. For morphological analysis, SEM studies for the prepared nanoparticles were performed. The chemical groups of the samples have been identified by FTIR studies. EDAX studies were carried out to identify the elements present in the samples.